“I want a measure of success”: the early writings of D. H. Lawrence and the literary marketplace - Grice, Annalise Lauran (2017)
This thesis offers a new perspective on D. H. Lawrence’s early career. Despite the ‘materialist turn’ in modernist studies, critics have not yet considered the extent and depth of Lawrence’s engagement with the literary marketplace. The labelling of him as a ‘genius’ who was destined to succeed has concealed the question of how he became a published writer in the first place. This is the first study to consider how Lawrence gained a foothold in the pre-WWI literary marketplace and began to make a name for himself. It re-evaluates aspects of Lawrence’s early oeuvre across a variety of genres, examining his multifaceted authorial identity as a novelist, essayist, lecturer, poet, journalist, short story writer, dramatist, and reviewer. The young author appeared in various guises as, for example, a romance writer, an ‘erotic’ writer, a Georgian poet, and a working-class realist. The fundamental principles underlying this work are that authors have plural identities, and their texts change under the pressure of immediate events (Jerome McGann); moreover, the literary field is a sociological phenomenon that is formed by networks of associations (Pierre Bourdieu). Using extensive new archival research, this thesis analyses the literary marketplace of the ‘long’ Edwardian period to assess the circumstances for becoming an author at this time. It examines Lawrence’s changing conceptions of what kind of writer he wanted to be, and who he wanted to write for; it reassesses the significance of Lawrence’s literary mentors, Ford Madox Hueffer and Edward Garnett, who helped Lawrence to become a published writer. In doing so, it recovers a number of figures (such as Violet Hunt, Ezra Pound, and Edward Marsh) whose significance for Lawrence’s career has been underestimated. This research evaluates how Lawrence’s work was marketed and received by the reading public in both Britain and America. It also examines several publishing houses (including Heinemann, Duckworth, T. Fisher Unwin, Elkin Mathews, and Mitchell Kennerley) and literary journals and magazines (for example the New Age, the English Review, Madame, Rhythm, and Forum). A new image emerges of Lawrence as a young writer who was pragmatic, diligent, and anxiously determined to achieve and sustain a career as a professional writer. From when he started writing in 1905, he had an idea of creativity as being produced collaboratively, and he asked for assistance from a variety of individuals. By 1914, he had attained a strong reputation on both sides of the Atlantic.